Oral direct factor Xa inhibition with edoxaban for thromboprophylaxis after elective total hip replacement - Raskob, Gary; Cohen, Alexander T.; Eriksson, Bengt I.; Puskas, David; Shi, Minggao; Bocanegra, Tomas; Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2010)
Edoxaban is a new oral direct factor Xa inhibitor. The purpose of this study was to evaluate the efficacy and safety of different doses of edoxaban for the prevention of venous thromboembolism (VTE) in patients undergoing elective total hip replacement. A total of 903 patients were randomised to oral edoxaban 15, 30, 60 or 90 mg once daily or subcutaneous dalteparin once daily (initial dose 2,500 IU, subsequent doses 5,000 IU). Both drugs were begun 6–8 hours postoperatively and continued for 7–10 days, when bilateral venography was performed. The primary efficacy endpoint was the incidence of total VTE, which included proximal and/or distal deep-vein thrombosis (DVT) by venography or symptomatic, objectively confirmed DVT or pulmonary embolism during the treatment period. The primary safety outcome was the incidence of the composite of major and clinically relevant non-major bleeding. All venograms and bleeding events were reviewed by a central independent adjudication committee blinded as to treatment allocation. Of the 903 patients randomised, 776 were evaluable for the primary efficacy analysis. The incidences of VTE were 28.2%, 21.2%, 15.2%, and 10.6% in patients receiving edoxaban 15, 30, 60 and 90 mg, respectively, compared with 43.8% in the dalteparin group (p<0.005 ). There was a statistically significant (p<0.001) dose-response for efficacy across the edoxaban dose groups for total VTE and for major VTE. The incidence of clinically relevant bleeding was low and similar across the groups. Oral edoxaban once daily is effective for preventing VTE after total hip replacement.
Keywords: Thromboprophylaxis; anticoagulant therapy; venous thromboembolism; factor Xa inhibitor; edoxaban